Chemical evidence for the effect of Urochloa ruziziensis on glyphosate-resistant soybeans - Nepomuceno, Mariluce [UNESP]; Chinchilla, Nuria; Varela, Rosa M.; Molinillo, Jose M. G.; Lacret, Rodney; Alves, Pedro L. C. A. [UNESP]; Macias, Francisco A. (Wiley-Blackwell, 2017)
BACKGROUND: Soybean (Glycine max) is an important oleaginous legume that has been cultivated in new areas in Brazil, including pastures. Problems of reduced production yields have been reported by soybean growers when the crop is sown immediately after desiccation of pastures of Urochloa spp. using glyphosate. The objective of this work was to extract, isolate and identify the major chemicals from U. ruziziensis that have phytotoxic activity and to evaluate the possible relation between this effect and reduced soybean yield. RESULTS: U. ruziziensis plants at the flowering stage were desiccated using glyphosate at 1.44 kg ha(-1). The plants were collected between five and ten days after treatment. Extracts of dried and ground shoots were obtained by sequential extraction with hexane, dichloromethane and methanol. The results of wheat coleoptile bioassays indicated that the methanol extract was more inhibitory than the dichloromethane extract regardless of glyphosate application. CONCLUSION: Protodioscin, a steroidal saponin, was isolated from the extract as the major component and the activities of this compound were in good agreement with those found for the extract. The release of this compound into the soil is a plausible explanation for the decrease in production observed in transgenic soybean crop after desiccation of U. ruziziensis. (c) 2017 Society of Chemical Industry
Keywords: soybean; glyphosate; protodioscin; Urochloa ruziziensis; allelopathy